Role-play and the world as stage in the comedia - Thacker, Jonathan (Liverpool Music Symposium., 2002)
The theatrum mundi metaphor was well-known in the Golden Age, and was often employed, notably by Calderón in his religious theatre. However, little account has been given of the everyday exploitation of the idea of the world as stage in the mainstream drama of the Golden Age. This study examines how and why playwrights of the period time and again created characters who dramatise themselves, who re-invent themselves by performing new roles and inventing new plots within the larger frame of the play. The prevalence of metatheatrical techniques among Golden Age dramatists, including Lope de Vega.